Implementation of the Criteria Comparison Matrix to reduce costs in a Textile company (LACCEI, 2024)
This article aims to show the impact of the implementation of engineering tools in the mitigation of problems present in the production and logistics áreas in a textile company located in the district of San Miguel (Lima-Peru) the problem being the high rate of materials refusal to suppliers generating stops due to lack of the main material causing an increase in the cost of production. Consequently, a need appears regarding the possible solutions for this problem. To meet this objective, the Criteria Comparison Matrix tool was proposed after a previous evaluation of realistic restrictions, historical data of the main and secondary suppliers was used for the design, the study was complemented with the linear regression simulation, resulting in a reduction in production costs of a total of S/ 160.00 per month. Finally, the economic viability of the implementation was evaluated, resulting in an IRR of 17%, a NPV of S/ 1,275.44, in addition to a B/C of 7.51.